2007
DOI: 10.7326/0003-4819-146-3-200702060-00008
|View full text |Cite
|
Sign up to set email alerts
|

Brief Communication: National Quality-of-Care Standards in Home-Based Primary Care

Abstract: Background: Home-based primary care for homebound seniors is complex, and practice constraints are unique. No quality-of-care standards exist. Objective:To identify process quality indicators that are essential to high-quality, home-based primary care.Design: An expert development panel reviewed established and new quality indicators for applicability to home-based primary care. A separate national evaluation panel used a modified Delphi process to rate the validity and importance of the potential quality indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…This modality allows the health professional not only to provide care for the client but also to educate caregivers and/or families so that they become secure and capable of carrying on with the health professional's work (17). It is important to identify nutritional and dietary status actions since they can contribute as quality indicators to monitor health care, quality of life and longevity in the geriatric population (18,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…This modality allows the health professional not only to provide care for the client but also to educate caregivers and/or families so that they become secure and capable of carrying on with the health professional's work (17). It is important to identify nutritional and dietary status actions since they can contribute as quality indicators to monitor health care, quality of life and longevity in the geriatric population (18,19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Previously developed quality-of-care standards for homebased primary care are relatively conditionspecific and not widely used. 27 In the absence of quality standards tailored to home-based medical care, practices that are motivated to measure the quality of care they provide, for the purpose of performance reporting or to engage in value-based care arrangements, are compelled to use currently available diseasespecific quality metrics. These metrics usually do not apply to the complex health needs or even the health status of the patients of these practices and thus could create pressure to provide the wrong type of care for their patients.…”
Section: Home-based Medical Care Exists In a Quality Desertmentioning
confidence: 99%
“…Higashi et al (2005) showed these ACOVE process indicators to be associated with improved survival. Recently, Smith, Soriano, and Boal (2007) published a subsequent set of quality indicators based on the ACOVE set that focused specifi cally on the care of vulnerable patients who received primary care in the home. Th is Home-Based Primary Care Quality Indicator Set (Annals of Internal Medicine, 2007) may be read in its entirety at http://www.annals.org.…”
Section: Quality Measurement In Home-based Primary Carementioning
confidence: 99%
“…Recommendations for screening tests such as mammography and colonoscopy must be weighed against the patient's expected life span, preferences, benefi t, and willingness to undergo treatment if the target condition is found (American Geriatrics Society Ethics Committee, 2007). Preventive examinations and interventions with regard to falls and gait screening, nutrition, polypharmacy, continence, and cognitive functioning Home-Based Primary Care Quality Indicator (Smith et al, 2007).…”
Section: Illness and Injury Preventionmentioning
confidence: 99%